Self-oxidation-resistant Sa-SBS polymer and preparation method thereof, SBS asphalt coating material, composition and preparation method thereof, and waterproofing membrane

By introducing hindered phenol into SBS for grafting reaction, self-antioxidation Sa-SBS polymer is generated, which solves the problem of poor phase separation and aging resistance in asphalt waterproof rolls, and significantly improves the resistance of asphalt waterproof rolls. Aging and low temperature performance and reduce costs.

CN118702845BActive Publication Date: 2024-12-24KESHUN WATERPROOF TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410830839.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-25
Publication Date
2024-12-24
Estimated Expiration
2044-06-25

AI Technical Summary

Technical Problem

The existing SBS has problems of phase separation and poor aging resistance in asphalt waterproof coils, especially because its alkenyl functional groups are prone to react with oxygen, resulting in a degradation in performance.

Method used

The self-antioxidized Sa-SBS polymer is grafted and the addition of hindered phenols makes the alkenyl functional groups in its structure epoxidize, forming epoxy functional groups, and reacting with asphalt surface groups to enhance the stability of asphalt and Aging resistance.

Benefits of technology

Effectively prevent the phase separation between SBS and asphalt, significantly improve the aging resistance and low temperature performance of asphalt waterproof rolls, extend the service life of the product, and reduce the amount of SBS and reduce the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118702845B_ABST
    Figure CN118702845B_ABST
Patent Text Reader

Abstract

The present application discloses a self-antioxidant Sa-SBS polymer and a preparation method, an SBS asphalt coating material, a composition and a preparation method, and a waterproof roll. The preparation method of the self-antioxidant Sa-SBS polymer comprises: dispersing 20PHR to 30PHR of SBS using 100PHR of solvent to obtain an SBS dispersion; adding formic acid and hydrogen peroxide to the SBS dispersion, mixing and keeping warm to obtain a reaction mixture; adding 1PHR to 5PHR of hindered phenol to the reaction mixture and heating to 80°C to 100°C to react, to obtain a self-antioxidant Sa-SBS polymer. The preparation method of the self-antioxidant Sa-SBS polymer of the present application adopts a simple and efficient grafting reaction to graft SBS with hindered phenol to obtain a hindered phenol grafted modified self-antioxidant Sa-SBS polymer, which changes the polarity of SBS to make it closer to the polarity of asphalt, and adds phenolic functional groups to the surface of the modified SBS. After the self-antioxidant Sa-SBS polymer is applied to asphalt coating, it can react with the groups on the surface of asphalt, thereby increasing the stability and aging resistance of asphalt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of building waterproof materials, and in particular relates to a self-antioxidant Sa-SBS polymer and a preparation method thereof, an SBS asphalt coating material, a composition and a preparation method thereof, and a waterproof roll. Background Art

[0002] At present, thermoplastic elastomer polystyrene-butadiene-styrene triblock polymer (Styrene-Butadiene-Styrene, SBS) is the most commonly used asphalt modifier in asphalt waterproofing membranes, which has a significant improvement on the high-temperature aging resistance and low-temperature bending resistance of asphalt. However, there are differences between the matrix asphalt and SBS in terms of structure, molecular weight, polarity, etc. During long-term storage, SBS-modified asphalt will undergo phase separation between SBS and asphalt, resulting in performance problems that do not meet the standards after 3 months or more. In addition, the polybutadiene (PB) chain segment of SBS contains double bonds, so the presence of unsaturated bonds will cause it to react easily with oxygen during long-term aging, and the aging resistance will drop sharply. Summary of the invention

[0003] In a first aspect, the present application provides a self-antioxidant Sa-SBS polymer having the following general structural formula:

[0004]

[0005] In formula (1), n=1-18; a+d=450-1400, b+c=1900-5700.

[0006] In one embodiment of the present application, in the self-oxidative Sa-SBS polymer, the mass ratio of the styrene segment to the butadiene segment is 3-3.5:6.5-7, and the content of the alkenyl functional group is ≤5%.

[0007] In one embodiment of the present application, the grafting rate of hindered phenol in the self-antioxidant Sa-SBS polymer is 0.2% to 5.0%.

[0008] In a second aspect, an embodiment of the present application provides a method for preparing a self-antioxidant Sa-SBS polymer, comprising:

[0009] Dispersing 20 PHR to 30 PHR of SBS with 100 PHR of a solvent capable of dissolving SBS to obtain an SBS dispersion;

[0010] Adding 10 PHR to 15 PHR of formic acid and 10 PHR to 15 PHR of hydrogen peroxide to the SBS dispersion, mixing and keeping warm to obtain a reaction mixture;

[0011] 1 PHR to 5 PHR of hindered phenol is added to the reaction mixture and the temperature is raised to 80° C. to 100° C. to react to obtain a self-antioxidant SBS polymer.

[0012] In the examples of the present application, SBS is modified by adding formic acid and hydrogen peroxide to a SBS dispersion, so that the alkenyl functional groups in the SBS structure undergo epoxidation reaction to generate epoxy functional groups, thereby obtaining modified SBS.

[0013] In one embodiment of the present application, the method for preparing the self-antioxidant Sa-SBS polymer further includes:

[0014] The prepared self-oxidation-resistant Sa-SBS polymer is added into the cooling liquid to cool the self-oxidation-resistant Sa-SBS polymer for forming:

[0015] The self-oxidation-resistant Sa-SBS polymer and the cooling liquid are filtered to remove unreacted organic matter and the cooling liquid.

[0016] In some embodiments of the present application, SBS is a polystyrene-butadiene-styrene triblock polymer (Styrene-Butadiene-Styrene), the molecular weight of SBS is 150,000 to 450,000, and the mass content of styrene segments in SBS is 20% to 30%.

[0017] In some embodiments of the present application, the solvent capable of dissolving SBS is selected from cyclohexane, toluene, CCl4, and CHCl3.

[0018] In some embodiments of the present application, the hindered phenol is selected from the reaction product of β-(4-hydroxyphenyl-3,5-di-tert-butyl)propionic acid and a C1-C18 alkyl alcohol.

[0019] In some embodiments of the present application, the hindered phenol is selected from methyl β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, n-octyl β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, n-dodecyl β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, n-octyl β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, or a combination thereof.

[0020] In one embodiment of the present application, the molecular formula of β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate is: 35 H 62 O3.

[0021] In some embodiments of the present application, the cooling liquid is an aqueous solution containing ethanol, and the concentration of the cooling liquid is sufficient to dissolve the residual organic matter in the antioxidant SBS polymer.

[0022] In the third aspect, an embodiment of the present application provides an SBS asphalt coating composition, comprising: 100PHR of asphalt, the asphalt is selected from 70# asphalt, 90# asphalt or a combination thereof; 5PHR to 10PHR of asphalt softening oil; 3PHR to 5PHR of the above-mentioned self-antioxidant Sa-SBS polymer; 2PHR to 4PHR of styrene-butadiene rubber; 30PHR to 50PHR of rubber powder; and 50PHR to 70PHR of powder.

[0023] In some embodiments of the present application, the asphalt softening oil is selected from at least one of base oil, cycloparaffinic oil, soybean oil, and aromatic oil.

[0024] In some embodiments of the present application, the rubber powder is 60-80 mesh tire rubber powder, wherein the mass content of rubber is 30%-50%, and the mass content of ash is 10%-30%.

[0025] In some embodiments of the present application, the powder is 180-200 mesh, and the powder is selected from heavy calcium powder, ore powder, concrete stone powder, talcum powder or a combination thereof.

[0026] In the fourth aspect, an embodiment of the present application provides a method for preparing an SBS asphalt coating, comprising: evenly dispersing 100 PHR of the above-mentioned asphalt and 5 PHR to 10 PHR of asphalt softening oil and heating the temperature to 130°C to 155°C to obtain an asphalt dispersion; adding 3 PHR to 5 PHR of the above-mentioned self-antioxidant Sa-SBS polymer and 2 PHR to 4 PHR of styrene-butadiene rubber to the asphalt dispersion and heating the temperature to 160°C to 180°C to obtain a blend containing self-antioxidant Sa-SBS polymer and styrene-butadiene rubber; adding 30 PHR to 50 PHR of rubber powder and 50 PHR to 70 PHR of powder to the blend containing self-antioxidant Sa-SBS polymer and styrene-butadiene rubber and heating the temperature to 180°C to 190°C to evenly disperse the mixture to obtain an SBS asphalt coating.

[0027] In one embodiment of the present application, 30PHR to 50PHR of rubber powder and 50PHR to 70PHR of powder are added to a blend containing self-antioxidant Sa-SBS polymer and styrene-butadiene rubber, and the temperature is raised to 180°C to 190°C to disperse evenly, which includes: adding 30PHR to 50PHR of rubber powder to the blend containing self-antioxidant Sa-SBS polymer and styrene-butadiene rubber and the temperature is raised to 180°C to 190°C to disperse, to obtain a blend containing rubber powder; adding 50PHR to 70PHR of powder to the blend containing rubber powder and maintaining the temperature at 180°C to 190°C until it is evenly dispersed, to obtain an SBS asphalt coating.

[0028] In another embodiment of the present application, adding 30PHR to 50PHR of rubber powder and 50PHR to 70PHR of powder to a blend containing self-antioxidant Sa-SBS polymer and styrene-butadiene rubber and heating the temperature to 180°C to 190°C to disperse evenly comprises: adding 50PHR to 70PHR of powder to the blend containing self-antioxidant Sa-SBS polymer and styrene-butadiene rubber and heating the temperature to 180°C to 190°C to disperse evenly to obtain a blend containing powder; adding 30PHR to 50PHR of rubber powder to the blend containing powder and maintaining the temperature at 180°C to 190°C to disperse evenly to obtain SBS asphalt coating.

[0029] In a fifth aspect, an SBS asphalt coating is prepared according to the above-mentioned method for preparing the SBS asphalt coating.

[0030] In the sixth aspect, an embodiment of the present application provides a waterproof roll material, comprising: a main reinforcing substrate, an SBS asphalt coating formed by the above-mentioned SBS asphalt coating composition coated on at least one side of the main reinforcing substrate, or an SBS asphalt coating prepared according to the above-mentioned SBS asphalt coating preparation method, and an isolation protective layer covering the asphalt coating.

[0031] In some embodiments of the present application, the main body reinforcement substrate is a main body reinforcement substrate formed by a main body reinforcement material, and the main body reinforcement material is one of a polyester substrate, a glass fiber substrate, and a glass fiber reinforced polyester substrate.

[0032] The self-antioxidant Sa-SBS polymer and the preparation method thereof of the embodiments of the present application adopt a simple and efficient grafting reaction, that is, SBS is grafted with hindered phenol to obtain a self-antioxidant Sa-SBS polymer modified by hindered phenol grafting, which changes the polarity of SBS to make it closer to the polarity of asphalt, and adds phenolic functional groups to the surface of the modified SBS. After the self-antioxidant Sa-SBS polymer is applied to asphalt coating, it can react with the groups on the surface of asphalt, thereby increasing the stability and aging resistance of asphalt. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solution of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0034] Figure 1 1 is a schematic flow chart of a method for preparing a self-antioxidant Sa-SBS polymer according to an embodiment of the present application;

[0035] Figure 2 is a hydrogen nuclear magnetic resonance spectrum of the compound having the structure shown in formula (2);

[0036] Figure 3 It is a schematic diagram of a process for preparing a SBS asphalt coating material provided in an embodiment of the present application;

[0037] Figure 4 It is a schematic diagram of the structure of the waterproof membrane provided in an embodiment of the present application.

[0038] Description of reference numerals:

[0039] 1. Main reinforcement substrate; 2. SBS asphalt coating material; 3. Release protective layer. DETAILED DESCRIPTION

[0040] The features and exemplary embodiments of various aspects of the present application will be described in detail below. In order to make the purpose, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only intended to explain the present application, rather than to limit the present application. For those skilled in the art, the present application can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present application by illustrating the examples of the present application.

[0041] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the statement "include..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.

[0042] The existing SBS preparation is to first add cyclohexane and styrene, then add alkyl lithium initiator, add butadiene after styrene polymerization is completed, and then complete butadiene and styrene polymerization to obtain polymer. Add styrene after the polymer reaction is completed, so as to obtain polystyrene butadiene styrene triblock polymer (Styrene-Butadiene-Styrene, abbreviated as SBS). In addition, it is also possible to add a coupling agent of different active groups after the reaction of styrene and butadiene polymer is obtained to terminate the reaction, so as to obtain different blocks or star-shaped SBB. In the SBS polymer, not only there is a carbon-carbon double bond in the styrene structural unit, but also there is a carbon-carbon double bond in the structural unit of butadiene. Under the catalytic action of the initiator, the carbon-carbon double bond of the block in SBS can be opened, and different active groups are introduced in the existing SBS, so that the functional groups of other functions can undergo addition reaction therewith, and SBS with different functions is obtained, making up for the functional groups that the original SBS does not have.

[0043] In view of the problems pointed out in the background technology, a technical solution is proposed to chemically modify SBS to improve the anti-aging performance of asphalt. Common chemical modification methods of SBS include catalytic hydrogenation, grafting modification, epoxidation modification, sulfonation modification, halogenation modification, thiol click reaction, etc. Among them, compared with the other methods mentioned above, the grafting modification reaction is simple and easy to react, has high selectivity, and can meet the needs of product customization. However, there are many types of SBS available. Although the method of grafting modification of SBS asphalt has achieved the effect of modifying asphalt, SBS will be degraded over time in the external environment. Compared with the structure formed by chemical reaction during the long-term storage of asphalt, it does not have long-term stability. The technology of SBS with anti-aging performance has not yet been disclosed. In addition, the existing SBS modified materials also have the defect that the preparation process is relatively cumbersome.

[0044] The inventors of the present application proposed a technical solution for chemically modifying SBS to improve the aging resistance of asphalt during the study of the prior art.

[0045] Self-antioxidant Sa-SBS polymer

[0046] The present application embodiment provides a self-antioxidant Sa-SBS polymer having the following general structural formula:

[0047]

[0048] In formula (1), n=1-18; a+d=450-1400, b+c=1900-5700.

[0049] In the embodiments of the present application, the self-antioxidant Sa-SBS polymer is in the form of white granules or powder.

[0050] In one embodiment of the present application, in the self-oxidative Sa-SBS polymer, the mass ratio of the styrene segment to the butadiene segment is 3-3.5:6.5-7, and the content of the alkenyl functional group is ≤5%.

[0051] In one embodiment of the present application, the grafting rate of hindered phenol in the self-antioxidant Sa-SBS polymer is 0.2% to 5.0%.

[0052] Preparation method of self-antioxidant Sa-SBS polymer

[0053] Figure 1 The method for preparing the self-antioxidant Sa-SBS polymer provided in the embodiment of the present application is shown, comprising:

[0054] S1. Disperse 20 PHR to 30 PHR of SBS using 100 PHR of a solvent capable of dissolving SBS to obtain an SBS dispersion;

[0055] S2, adding 10PHR-15PHR of formic acid and 10PHR-15PHR of hydrogen peroxide to the SBS dispersion, mixing and heat preservation to obtain a reaction mixture;

[0056] S3. Add 1 PHR to 5 PHR of hindered phenol to the reaction mixture and heat to 80° C. to 100° C. to react to obtain a self-antioxidant Sa-SBS polymer.

[0057] In the examples of the present application, formic acid and hydrogen peroxide are added to the SBS dispersion to cause the SBS to undergo an epoxidation reaction to obtain epoxidized modified SBS, and then the modified SBS is reacted with hindered phenol to prepare a self-antioxidant Sa-SBS polymer.

[0058] In some embodiments of the present application, SBS is a polystyrene-butadiene-styrene triblock polymer (Styrene-Butadiene-Styrene), the molecular weight of SBS is 150,000 to 450,000, and the mass content of styrene segments in SBS is 20% to 30%.

[0059] In some embodiments of the present application, the solvent capable of dissolving SBS is selected from cyclohexane, toluene, CCl4, and CHCl3.

[0060] In one embodiment of the present application, the solvent capable of dissolving SBS is toluene, wherein 100 PHR of toluene can be heated to 30° C. to 50° C. to accelerate the dissolution rate of SBS.

[0061] In some embodiments of the present application, SBS (styrene butadiene styrene block polymer) is at least one of LG501, 1401, 3411, and 7551.

[0062] In some embodiments of the present application, the hindered phenol is the product of the reaction of β-(4-hydroxyphenyl 3,5-di-tert-butyl) propionic acid and C1-C18 alkyl alcohol. The C1-C18 alkyl alcohol is selected from monohydric alcohol and dihydric alcohol. Among them, the monohydric alcohol is selected from methanol, ethanol, propanol, 2-propanol, n-butanol, isobutanol, n-pentanol, isopentanol, neopentyl alcohol, n-hexanol, n-heptanol, n-octanol, n-nonanol, 11-carbon alcohol, 12-carbon alcohol, 13-carbon alcohol, 14-carbon alcohol, 15-carbon alcohol, 16-carbon alcohol, 17-carbon alcohol, 18-carbon alcohol or a combination thereof. The dihydric alcohol is selected from ethylene glycol, propylene glycol, 1,2-propylene glycol, butanediol, pentanediol, hexanediol, heptanediol, octanediol, nonanediol, decanediol, 11-carbon glycol to 18-carbon glycol or a combination thereof.

[0063] In some embodiments of the present application, the hindered phenol is selected from methyl β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, n-octadecanol β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, n-dodecyl β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, n-octyl β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, or a combination thereof.

[0064] In one embodiment of the present application, the hindered phenol is β-(4-hydroxyphenyl 3,5-di-tert-butyl) propionate, having the molecular formula: 35 H 62 O3, CAS number: 2082-79-3.

[0065] In some embodiments of the present application, the method for preparing a self-antioxidant Sa-SBS polymer further includes: adding the prepared self-antioxidant Sa-SBS polymer to a coolant to cool and mold the self-antioxidant SBS polymer; and filtering the self-antioxidant Sa-SBS polymer and the coolant to remove unreacted organic matter and the coolant.

[0066] In the present application, the self-antioxidant Sa-SBS polymer just obtained is obtained by reaction under the conditions of 80°C to 100°C, and its temperature is still relatively high relative to room temperature. Therefore, it is necessary to add the obtained self-antioxidant Sa-SBS polymer into a coolant for cooling, and then separate the self-antioxidant Sa-SBS polymer and the coolant by filtration, and at the same time use the coolant to separate the unreacted organic matter from the product to obtain the hindered phenol-modified self-antioxidant Sa-SBS polymer.

[0067] In some embodiments of the present application, the coolant is selected from compounds that do not react with the self-antioxidant Sa-SBS polymer and can dissolve organic matter in the process of preparing the self-antioxidant Sa-SBS polymer to separate the organic matter from the self-antioxidant Sa-SBS polymer mixed solution and facilitate the subsequent separation process.

[0068] In one embodiment of the present application, the coolant is an aqueous solution selected from ethanol and propanol, and its concentration is sufficient to dissolve the residual organic matter in the antioxidant SBS polymer. Exemplarily, the mass concentration of ethanol in the aqueous solution of ethanol is 2% to 100%, for example, 3%, 5%, 10%, 20%, 30%, 50%, 56%, 64%, 72%, 75%, 81%, 88%, 90%, 99%, etc., or any combination range of the above values, or any combination range of numerical values ​​between the above values.

[0069] The self-antioxidant Sa-SBS polymer of the present application changes the polarity of SBS by grafting hindered phenol compounds into SBS, so that the polarity of the self-antioxidant Sa-SBS polymer is closer to the polarity of asphalt, and phenolic functional groups are added to the surface of the modified self-antioxidant Sa-SBS polymer, which can react with the groups on the surface of asphalt, thereby increasing the stability and aging resistance of asphalt. Therefore, after applying it to asphalt waterproofing membrane, it can greatly improve the durability of asphalt waterproofing membrane and prevent the phase separation of SBS modified asphalt in the waterproofing membrane.

[0070] Confirmation of Self-Antioxidant SBS Polymer

[0071] The present application confirms that the compound prepared by the reaction of modified SBS and hindered phenol is a self-antioxidant Sa-SBS polymer by the characteristic peak method of nuclear magnetic resonance hydrogen spectrum.

[0072] Taking the reaction of modified SBS with hindered phenol (β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate) to generate the compound of the following formula (2) as an example, the preparation process includes:

[0073] A1. Disperse 25 PHR of SBS with 100 PHR of toluene and heat to 35° C. to obtain an SBS dispersion;

[0074] A2, adding 12 PHR of formic acid and 12 PHR of hydrogen peroxide to the SBS dispersion, mixing and keeping warm for 30 min to obtain a reaction mixture;

[0075] A3, adding 5 PHR of hindered phenol β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate n-octadecyl alcohol ester to the reaction mixture and heating to 100° C. to react to obtain a mixture containing the self-antioxidant Sa-SBS polymer obtained by formula (2);

[0076] A4, adding the mixture containing the self-antioxidant Sa-SBS polymer obtained by formula (2) into a cooling liquid (an ethanol solution with a mass concentration of 20%) to cool the mixture containing the self-antioxidant Sa-SBS polymer obtained by formula (2) to form;

[0077] A5. Filter the mixture of the self-antioxidant Sa-SBS polymer obtained by formula (2) and the cooling liquid to remove the unreacted organic matter and the cooling liquid, and obtain the self-antioxidant Sa-SBS polymer.

[0078]

[0079] Testing process:

[0080] After the reaction of hindered phenol and modified SBS is completed, the self-antioxidant Sa-SBS polymer is washed to remove the hindered phenol and modified SBS therein. The self-antioxidant Sa-SBS polymer from which the hindered phenol and modified SBS are removed is tested by nuclear magnetic resonance hydrogen spectrum. Figure 2 As shown, a characteristic peak appears at the position of 5.35 ppm, which is mainly attributed to the phenolic hydroxyl group in the self-antioxidant Sa-SBS polymer. This is a special structural peak that appears in the structure of the self-antioxidant Sa-SBS polymer after successful grafting. Since the self-antioxidant Sa-SBS polymer has been cleaned to remove the hindered phenol, the phenolic hydroxyl group in the hindered phenol is excluded, and only the phenolic hydroxyl group exists in the self-antioxidant Sa-SBS polymer. Therefore, it can be determined by the characteristic peak of the phenolic hydroxyl group at the position of 5.35 ppm that the self-antioxidant Sa-SBS polymer in the present application has been successfully grafted with the (β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionic acid n-octadecyl ester.

[0081] Application of Self-Antioxidant SBS Polymer

[0082] The above-mentioned self-antioxidant Sa-SBS polymer can be used as a component in asphalt coatings for waterproof roll materials, and can also be used as a modifier component in asphalt modification, coatings, and adhesives.

[0083] SBS asphalt coating composition

[0084] In order to solve the problems existing in the prior art, the present application provides an SBS asphalt coating composition and a method for preparing the SBS asphalt coating. The preparation method of the SBS asphalt coating composition provided in the present application is first introduced below.

[0085] The SBS asphalt coating composition of the embodiment of the present application includes: 100PHR of asphalt, the asphalt is selected from 70# asphalt, 90# asphalt or a combination thereof; 5PHR to 10PHR of asphalt softening oil; 3PHR to 5PHR of the above-mentioned self-antioxidant Sa-SBS polymer; 2PHR to 4PHR of styrene-butadiene rubber; 30PHR to 50PHR of rubber powder; and 50PHR to 70PHR of powder.

[0086] In some embodiments of the present application, the asphalt softening oil is at least one of base oil, cycloparaffinic oil, soybean oil, and aromatic oil.

[0087] In some embodiments of the present application, the rubber powder is 60-80 mesh tire rubber powder, wherein the mass content of rubber is 30%-50%, and the mass content of ash is 10%-30%.

[0088] In some embodiments of the present application, the powder is 180 mesh to 200 mesh, and the powder is selected from heavy calcium powder, mineral powder, concrete stone powder, talcum powder or a combination thereof. Exemplarily, the powder is heavy calcium powder alone. Or the powder is a mixture of heavy calcium powder and mineral powder in a mass ratio of 1: to 5. The powder includes a mixture of mineral powder and concrete stone powder in a mass ratio of 1: 0.5 to 3. Or the powder is a mixture of heavy calcium powder, mineral powder, and concrete stone powder in any mass ratio.

[0089] In some embodiments of the present application, the styrene-butadiene rubber may be selected from brands such as PetroChina 1502, Kunlun 1502, Li Changrong 1502 or a combination thereof.

[0090] Preparation method of SBS asphalt coating material

[0091] Figure 3 FIG. 1 is a schematic diagram showing a process for preparing a SBS asphalt coating material provided by an embodiment of the present application. Figure 3 As shown, the preparation method of the SBS asphalt coating material of the embodiment of the present application includes:

[0092] S1. Disperse 100 PHR of asphalt and 5 PHR to 10 PHR of asphalt softening oil evenly and heat to 130° C. to 155° C. to obtain an asphalt dispersion;

[0093] S2, adding 3PHR to 5PHR of self-antioxidant Sa-SBS polymer and 2PHR to 4PHR of styrene-butadiene rubber to the asphalt dispersion and heating to 160° C. to 180° C. to obtain a blend containing the self-antioxidant Sa-SBS polymer and styrene-butadiene rubber;

[0094] S3. Add 30PHR to 50PHR of rubber powder and 50PHR to 70PHR of powder to the blend containing self-antioxidant Sa-SBS polymer and styrene-butadiene rubber, raise the temperature to 180°C to 190°C and disperse evenly to obtain SBS asphalt coating material.

[0095] In one embodiment of the present application, 30PHR to 50PHR of rubber powder and 50PHR to 70PHR of powder are added to a blend containing a self-oxidizing Sa-SBS polymer and styrene-butadiene rubber and the mixture is heated to 180° C. to 190° C. and dispersed uniformly, including:

[0096] Adding 30 PHR to 50 PHR of rubber powder to a blend containing a self-antioxidant Sa-SBS polymer and styrene-butadiene rubber and heating the mixture to 180° C. to 190° C. for dispersion to obtain a blend containing rubber powder;

[0097] Add 50PHR to 70PHR of powder to the blend containing rubber powder and maintain the temperature at 180°C to 190°C until it is evenly dispersed to obtain SBS asphalt coating material.

[0098] In another embodiment of the present application, 30PHR to 50PHR of rubber powder and 50PHR to 70PHR of powder are added to a blend containing a self-oxidizing Sa-SBS polymer and styrene-butadiene rubber and the mixture is heated to 180° C. to 190° C. and dispersed uniformly, including:

[0099] Adding 50 PHR to 70 PHR of powder to a blend containing a self-antioxidant Sa-SBS polymer and styrene-butadiene rubber and heating the mixture to 180° C. to 190° C. until the mixture is evenly dispersed, thereby obtaining a blend containing powder;

[0100] 30PHR-50PHR of rubber powder is added to the blend containing the powder and maintained at 180°C-190°C until it is evenly dispersed to obtain SBS asphalt coating material.

[0101] SBS asphalt coating

[0102] The SBS asphalt coating is prepared according to the above-mentioned preparation method.

[0103] Waterproof membrane

[0104] Figure 4 The schematic diagram of the structure of the waterproofing membrane provided by the embodiment of the present application is shown. The self-oxidation-resistant SBS waterproofing membrane comprises: a main reinforcement substrate 1, an asphalt coating 2 formed by the above-mentioned asphalt coating composition coated on at least one side of the main reinforcement substrate, or an asphalt coating 2 prepared according to the above-mentioned asphalt coating preparation method; and an isolation protective layer 3 covering the asphalt coating 2.

[0105] In some embodiments of the present application, the main reinforcement substrate is made of a main reinforcement material, and the main reinforcement material is one of a polyester substrate, a glass fiber substrate, and a glass fiber reinforced polyester substrate.

[0106] In one embodiment of the present application, the isolation protection layer is a single-sided release film made of transparent PET material, with a thickness of 0.01 mm to 0.1 mm, which is coated with solvent-free silicone oil and has a release force of 0.1 N / 25 mm to 0.5 N / 25 mm. Optionally, the thickness of the single-sided release film is 0.035 mm to 0.038 mm.

[0107] The waterproofing membrane of the present application can maintain high product performance during the production, transportation, storage and service process. After 7 days of thermal oxidative aging, its low-temperature flexibility can still be as low as -27°C; after 7 days of thermal oxidative aging, the bonding strength between the waterproofing membrane and the aluminum plate can still be as high as 1.95N / 50mm, proving that its aging resistance, low-temperature resistance and bonding performance are all good. On the other hand, the waterproofing membrane of the present application can also reduce costs. The developed waterproofing membrane has low cost, excellent performance, and also has good aging resistance.

[0108] Preparation method of waterproof membrane

[0109] The preparation method of the waterproofing membrane comprises: applying the prepared asphalt coating material to at least one side of the main reinforcing substrate to form an asphalt coating material of a certain thickness; placing an isolation protective layer on the side of the asphalt coating material away from the main reinforcing substrate, and after cooling, a self-oxidation-resistant Sa-SBS asphalt waterproofing membrane can be obtained.

[0110] In some embodiments of the present application, the thickness of the asphalt coating is 3.0 mm to 4.0 mm.

[0111] The asphalt coating can be squeezed by heavy metal rollers to evenly press the asphalt coating to form an asphalt coating layer with a certain thickness.

[0112] In one embodiment of the present application, the upper and lower sides of the main reinforcing substrate 1 are coated with asphalt coating material 2, and the isolation protective layer 3 is pressed on the upper and lower sides of the asphalt coating material 2 respectively. After cooling, a self-antioxidant Sa-SBS asphalt waterproof membrane with waterproof effect on both sides can be obtained.

[0113] The preparation method of the waterproofing coiled material of the embodiment of the present application improves the aging resistance and low temperature performance of the waterproofing coiled material. It also reduces the preparation cost of the SBS asphalt coating. On the other hand, the present application uses the hindered phenol-modified self-antioxidant Sa-SBS polymer and the SBS asphalt coating prepared therefrom, which changes the defects of the traditional asphalt waterproofing coiled material, which has a large amount of SBS and poor low temperature performance and aging resistance.

[0114] The technical solution of the present application is further illustrated below through specific embodiments and comparative examples.

[0115] Example

[0116] The following are the models and / or sources of some reagents and materials used in the examples or the requirements to be met:

[0117] Toluene, formic acid, hydrogen peroxide, hindered phenol, and ethanol all use MacLean reagent with a purity of 99%;

[0118] SBS (styrene-butadiene-styrene block polymer) is LG501;

[0119] The hindered phenol is n-octadecyl β-(-4-hydroxyphenyl-3,5-di-tert-butyl) propionate, CAS NO: 2082-79-3.

[0120] The manufacturer of 90# asphalt is Sinopec; the model of styrene butadiene rubber is Sinopec 1502, and styrene butadiene rubber is denoted by its English abbreviation SBR in the embodiments and comparative examples;

[0121] The rubber powder is 60-80 mesh tire rubber powder, with a rubber content of 30%-50% and an ash content of 10%-30%;

[0122] The powder is heavy calcium powder obtained by passing through a 200-mesh sieve; the powder is talcum powder obtained by passing through a 200-mesh sieve; the powder is concrete stone powder obtained by passing through a 200-mesh sieve;

[0123] The isolation protection layer is a single-sided release film made of transparent PET material with a thickness of 0.035mm. It is coated with solvent-free silicone oil and has a release force of 0.1N / 25mm to 0.5N / 25mm.

[0124] Examples 1-7

[0125] According to the raw material composition of the percentage content (PHR) in Table 1 below, the self-antioxidant Sa-SBS polymers of Examples 1-7 were prepared using the preparation method of the self-antioxidant Sa-SBS polymer of the present application example:

[0126] Table 1

[0127] Comparison Items Toluene, PHR SBS,PHR Formic acid, PHR Hydrogen peroxide, PHR Hindered Phenol, PHR SBS polymer labeling Example 1 100 25 12 12 5 N1 Example 2 100 28 10 12 5 N2 Example 3 100 25 15 10 5 N3 Example 4 100 28 10 15 5 N4 Example 5 100 22 15 10 5 N5 Example 6 100 25 12 12 1 N6 Example 7 100 25 12 12 3 N7

[0128] The self-antioxidant Sa-SBS polymer of Example 1 is prepared by the following method, comprising the steps of:

[0129] A1: Mix toluene and SBS according to the ratio in Table 1, keep stirring at 300 rpm, raise the temperature to 35°C, and keep the temperature for 1.5 hours until the SBS is completely dissolved, to obtain an SBS dispersion;

[0130] A2: Add formic acid and hydrogen peroxide to the SBS dispersion according to the ratio in Table 1, stir evenly, and keep warm for 30 minutes to obtain a reaction mixture;

[0131] A3: adding hindered phenol to the reaction mixture according to the ratio in Table 1, heating to 100° C., and shearing and dispersing at the temperature at a speed of 300 rpm for 35 min to obtain a mixture of self-antioxidant Sa-SBS polymer;

[0132] A4 slowly adds the mixed solution of the self-oxidative Sa-SBS polymer into the prepared ethanol solution with a mass concentration of 20%, so that the self-oxidative SBS polymer is formed and precipitated, that is, the self-oxidative Sa-SBS polymer is obtained, which is recorded as N1. The self-oxidative Sa-SBS polymers of Examples 2-7 are prepared using the raw materials with corresponding contents in Table 1 and through the same process steps and parameters as Example 1, and are recorded as N2-N7 respectively.

[0133] Comparative Examples 1-5

[0134] According to the raw material composition of the percentage content (PHR) in Table 2 below, the SBS polymers of Comparative Examples 1-5 were prepared:

[0135] Table 2

[0136]

[0137] Comparative Example 1

[0138] The difference between the preparation method of the self-antioxidant Sa-SBS polymer of Comparative Example 1 and Example 1 is that after SBS is dissolved in toluene, formic acid and hydrogen peroxide are added, and hindered phenol is not added. The order of adding other raw materials and the process parameters are the same as those of the preparation method of Example 1. The SBS polymer of Comparative Example 1 is prepared by the following method, including:

[0139] A1: Mix toluene and SBS according to the ratio in Table 2, stir the mixture at 300 rpm, heat it to 35°C and keep it warm for 1.5 hours until the SBS is completely dissolved, to obtain an SBS dispersion;

[0140] A2: Add formic acid and hydrogen peroxide to the SBS dispersion after heat preservation in step A1 according to the ratio, stir evenly, and keep the temperature for 30 minutes to obtain a reaction mixture;

[0141] A3: Slowly add the reaction mixture after shearing and dispersion in step A2 into the prepared ethanol solution with a mass concentration of 20% to form and precipitate the SBS polymer, thereby obtaining the SBS polymer, which is recorded as N8.

[0142] Comparative Example 2

[0143] The difference between the preparation method of the self-antioxidant Sa-SBS polymer of Comparative Example 2 and Example 1 is that after SBS is dissolved in a toluene solution, formic acid is added, and hydrogen peroxide and hindered phenol are not added. However, the order of adding other raw materials and the process parameters are the same as those of the preparation method of Example 1. The SBS polymer is prepared by the following method, including:

[0144] A1: Mix toluene and SBS according to the ratio, keep stirring the mixture at 300 rpm, and heat it to 35°C and keep it warm for 1.5 hours until the SBS is completely dissolved to obtain an SBS dispersion;

[0145] A2: Add formic acid to the SBS dispersion after heat preservation in step A1 according to the ratio, stir evenly, and keep warm for 30 minutes;

[0146] A3: shear the dispersed solution in step A2, and slowly add it into the prepared ethanol solution with a mass concentration of 20% to make SBS form and precipitate, thereby obtaining SBS polymer, which is recorded as N9.

[0147] Comparative Example 3

[0148] The difference between the preparation method of the self-antioxidant Sa-SBS polymer of Comparative Example 3 and Example 1 is that after SBS is dissolved in a toluene solution, hydrogen peroxide is added, and formic acid and hindered phenol are not added. However, the order of adding other raw materials and the process parameters are the same as those of the preparation method of Example 1. The SBS polymer is prepared by the following method, including:

[0149] A1: Mix toluene and SBS according to the ratio, keep stirring the mixture at 300 rpm, and heat it to 35°C and keep it warm for 1.5 hours until the SBS is completely dissolved to obtain an SBS dispersion;

[0150] A2 adds hydrogen peroxide to the mixture after keeping warm in step A1 according to the proportion, stirs evenly, and keeps warm for 30 minutes;

[0151] A3: shear the dispersed solution in step A2, and slowly add it into the prepared ethanol solution with a mass concentration of 20%, so that SBS is formed and precipitated, thereby obtaining SBS, which is recorded as N10.

[0152] Comparative Example 4

[0153] The difference between the preparation method of the self-antioxidant Sa-SBS polymer of Comparative Example 4 and Example 1 is that after SBS is dissolved in toluene, hindered phenol is added, and formic acid and hydrogen peroxide are not added. However, the order of adding other raw materials and the process parameters are the same as those of the preparation method of Example 1. The SBS polymer is prepared by the following method, including:

[0154] A1: Mix toluene and SBS according to the ratio, keep stirring the mixture at 300 rpm, and heat it to 35°C and keep it warm for 1.5 hours until the SBS is completely dissolved to obtain an SBS dispersion;

[0155] A2: Add hindered phenol to the SBS dispersion after heat preservation in step A1 according to the ratio, stir evenly, and keep warm for 30 minutes;

[0156] A3: Slowly add the mixed solution after shearing and dispersion in step A2 into the prepared ethanol solution with a mass concentration of 20% to form and precipitate the SBS polymer, thereby obtaining the SBS polymer, which is recorded as N11.

[0157] Comparative Example 5

[0158] The difference between the preparation method of the self-antioxidant Sa-SBS polymer of Comparative Example 5 and Example 1 is that after the SBS is dissolved in the toluene solution, no hydrogen peroxide, formic acid and hindered phenol are added. However, the order of adding other raw materials and the process parameters are the same as those of the preparation method of Example 1. The SBS polymer is prepared by the following method, including:

[0159] A1: Mix toluene and SBS according to the ratio, keep stirring the mixture at 300 rpm, and heat it to 35°C and keep it warm for 1.5 hours until the SBS is completely dissolved to obtain an SBS dispersion;

[0160] A2: shear the dispersed solution in step A1, slowly add it into the prepared ethanol solution with a mass concentration of 20%, so that SBS is formed and precipitated, thereby obtaining SBS polymer, which is recorded as N12.

[0161] Example 8-24

[0162] Examples 8-24 all provide a waterproof roll material, including a main reinforcement substrate 1, an SBS asphalt coating material 2 covering one side of the main reinforcement substrate 1, and an isolation protection layer 3 covering the outer side of the SBS asphalt coating material 2.

[0163] The SBS asphalt coating material of Example 8 is composed of the following raw materials with the following percentages (PHR): 90# asphalt, 100 PHR; asphalt softening oil, 5 PHR; self-antioxidant Sa-SBS polymer (N1), 3 PHR; SBR, 4 PHR; rubber powder, 30 PHR; heavy calcium powder, 70 PHR. The SBS asphalt coating material of Example 8 is prepared by the following method, including the following steps:

[0164] A1. Mix 90# asphalt and asphalt softening oil according to the ratio, stir the mixture at a speed of 1000 rpm, and heat it to 140℃~145℃ and keep it warm for 1.5h until the asphalt is completely melted to obtain asphalt dispersion;

[0165] A2, adding the self-oxidation-resistant Sa-SBS polymer (N1) and SBR to the asphalt dispersion after the insulation in step A1 according to the ratio, heating to 175° C. to 180° C. and keeping the temperature for 1.5 hours to obtain a blend containing the self-oxidation-resistant SBS polymer and SBR;

[0166] A3, adding rubber powder to the blend containing the self-antioxidant Sa-SBS polymer and SBR according to the proportion, heating to 180° C. to 185° C., and shearing and dispersing at the same temperature at a speed of 1000 rpm for 2.5 hours to obtain a blend containing rubber powder;

[0167] A4. Add heavy calcium powder to the blend containing rubber powder, and shear and disperse it at a temperature of 180°C to 185°C and a rotation speed of 1000 rpm for 1.5 hours to obtain SBS asphalt coating material.

[0168] The asphalt coatings of Examples 9-24 are respectively composed of raw materials with corresponding percentages in Table 3 below, and the asphalt coatings of Examples 9-24 are prepared according to the preparation method of the SBS asphalt coating of Example 8; the preparation method of the asphalt coatings of Examples 11 and 12-24 is the same as the preparation method of Example 8; the difference between the preparation method of the asphalt coatings of Examples 9 and 12 and the preparation method of the asphalt coating of Example 8 is that:

[0169] In Example 9, A3 is added with rubber powder and heated to 185°C to 190°C for shear dispersion, and A4 is added with heavy calcium powder and the temperature for shear dispersion is 185°C to 190°C;

[0170] In Example 12, A3 is added with rubber powder and the temperature is raised to 185°C to 190°C for shear dispersion, and A4 is added with heavy calcium powder and the temperature is also raised to 185°C to 190°C for shear dispersion.

[0171]

[0172] Comparative Examples 6-13

[0173] Comparative Examples 6-13 all provide a waterproof roll material, including a main reinforcement substrate 1, an SBS asphalt coating material 2 covering one side of the main reinforcement substrate 1, and an isolation protection layer 3 covering the outer side of the SBS asphalt coating material 2.

[0174] The SBS asphalt coating material of Comparative Example 6 is composed of the following raw materials with the following percentages (PHR): 90# asphalt, 100 PHR; asphalt softening oil, 5 PHR; SBS polymer (N8), 3 PHR; SBR, 4 PHR; rubber powder, 30 PHR; heavy calcium powder, 70 PHR. The SBS asphalt coating material of Comparative Example 6 is prepared by the following method, including the following steps:

[0175] A1. Mix 90# asphalt and asphalt softening oil according to the ratio, stir the mixture at a speed of 1000 rpm, and heat it to 140℃~145℃ and keep it warm for 1.5h until the asphalt is completely melted to obtain asphalt dispersion;

[0176] A2, adding SBS polymer (N8) and SBR to the asphalt dispersion after heat preservation in step A1 according to the ratio, heating to 175°C to 180°C and keeping the temperature for 1.5h to obtain a blend containing SBS polymer and SBR;

[0177] A3, adding rubber powder to the blend containing SBS polymer and SBR according to the proportion, heating to 180°C to 185°C, and shearing and dispersing at the same temperature at a speed of 1000 rpm for 2.5 hours to obtain a blend containing rubber powder;

[0178] A4. Add heavy calcium powder to the blend containing rubber powder, and shear and disperse it at a temperature of 180°C to 185°C and a rotation speed of 1000 rpm for 1.5 hours to obtain SBS asphalt coating material.

[0179] The asphalt coatings of Comparative Examples 7-13 are respectively composed of raw materials with corresponding percentages in Table 4 below, and the asphalt coatings of Comparative Examples 6-13 are prepared according to the preparation method of the SBS asphalt coating of Comparative Example 6; the preparation methods of the asphalt coatings of Comparative Examples 7-11 and Comparative Example 13 are the same as the preparation method of Comparative Example 6; the difference between the preparation method of the asphalt coating of Comparative Example 12 and the preparation method of the asphalt coating of Comparative Example 6 is that:

[0180] In Comparative Example 12, the temperature of A3 added with rubber powder was raised to 185°C-190°C for shear dispersion, and the temperature of A4 added with heavy calcium powder for shear dispersion was also raised to 185°C-190°C.

[0181]

[0182] The waterproof membranes prepared in Examples 8-24 and Comparative Examples 6-13 were tested for the following performance items:

[0183] 1. Aging performance test

[0184] Sample preparation and testing were carried out in accordance with Part 14 of the national standard GB / T 328-2007 "Test methods for building waterproof membranes". The aging conditions used were forced air oven heat aging at 70°C for 7 days and 14 days. The aging resistance test was carried out in accordance with the national standard BG 23441-2009.

[0185] 2. Low temperature flexibility test

[0186] The low temperature flexibility test method used is to prepare samples and test according to the national standard GB / T 328-2007 "Test methods for building waterproof membranes" Part 14. Among them, the low temperature flexibility of the material is tested to the limit, and the samples are prepared and tested according to the national standard GB / T 328-2007 "Test methods for building waterproof membranes" Part 14;

[0187] 3. Peel strength test

[0188] The aluminum plate peel strength test method used is based on the national standard GB 23441-2009 "Self-adhesive polymer modified asphalt waterproofing membrane" for sample preparation and testing. Among them, the aluminum plate peel strength takes the maximum value;

[0189] The test results of the above performances are summarized in Table 5 below:

[0190] Table 5 Performance test data of waterproof membranes prepared in Examples 8-24 and Comparative Examples 6-13

[0191]

[0192] Combining the contents of Examples 1-7, 8-24 and Comparative Examples 1-13 with the performance test results of Table 5, the following results are obtained:

[0193] Comparing the waterproofing membranes of Example 8 and Example 9, the self-antioxidant Sa-SBS polymer (N2) in Example 9 only increases the amount of SBS compared to the self-antioxidant Sa-SBS polymer (N1) in Example 8, and the other parts remain unchanged. However, the attenuation of the low-temperature performance of the waterproofing membranes of Example 8 and Example 9 before aging and after aging for 7 days is 2°C, with no significant difference. This shows that in the process of preparing the waterproofing membrane, only increasing the amount of SBS does not significantly help the attenuation of the low-temperature performance of the waterproofing membrane. The peel strength of the waterproofing membrane of Example 9 with an increased amount of SBS before and after aging is greater than the peel strength of the waterproofing membrane of Example 8.

[0194] Comparing the waterproofing membranes of Example 8 and Example 10, the self-oxidation-resistant Sa-SBS polymer (N3) in Example 10 only increases the amount of hydrogen peroxide compared to the self-oxidation-resistant Sa-SBS polymer (N1) in Example 8, and the amounts of other components remain unchanged. The low-temperature performance decay of the waterproofing membrane of Example 10 before aging and after aging for 7 days is 3°C, indicating that in the process of preparing the waterproofing membrane, increasing the amount of hydrogen peroxide has a negative impact on the waterproofing membrane's ability to prevent low-temperature performance decay. The peel strength of the waterproofing membrane of Example 10 is increased compared to that of Example 8.

[0195] Comparing the waterproofing membranes of Example 8 and Example 11, the self-antioxidant Sa-SBS polymer (N4) in Example 11 has increased hydrogen peroxide and SBS dosages compared to the self-antioxidant Sa-SBS polymer (N1) in Example 8, and the contents of other components remain unchanged. The low temperature performance decay of the waterproofing membrane of Example 8 before aging and after aging for 7 days is 2°C, and the low temperature performance decay of the waterproofing membrane of Example 11 before aging and after aging for 7 days is 3°C, indicating that in the process of preparing the waterproofing membrane, increasing the amount of hydrogen peroxide and SBS at the same time has a negative impact on the waterproofing membrane to prevent low temperature performance decay. The peel strength of the waterproofing membrane of Example 11 is increased compared with that of Example 8.

[0196] Compare the waterproof membranes of Example 8 and Example 12. The self-antioxidant Sa-SBS polymer (N5) in Example 12 only reduces the amount of SBS compared to the self-antioxidant Sa-SBS polymer (N1) in Example 8, while the other properties remain unchanged. The low-temperature performance decay of the waterproof membrane of Example 8 before aging and after aging for 7 days is 2°C, while the low-temperature performance decay of the waterproof membrane of Example 12 before aging and after aging for 7 days is 4°C, indicating that in the process of preparing the waterproof membrane, reducing the amount of SBS has a negative impact on preventing the waterproof membrane from attenuating at low temperatures. The peel strength of the waterproof membrane of Example 12 is significantly reduced, indicating that the reduction in the amount of SBS will have a significant adverse effect on the peel strength of the waterproof membrane.

[0197] Comparing Examples 13 and 14 with Example 8, the amount of hindered phenol in the self-antioxidant Sa-SBS polymer of the asphalt coating of Examples 13 and 14 is reduced from 5PHR to 1PHR and 3PHR respectively, but their extreme low temperature performance is basically the same as that of Example 8, maintained at 29°C; the low temperature performance after aging for 7 and 14 days is reduced compared with Example 8, but the peel strength before and after aging remains unchanged or increases.

[0198] Comparing Examples 15 and 16 with Example 8, Examples 15 and 16 increase the dosage of self-antioxidant Sa-SBS to 4 PHR and 5 PHR respectively, and their low temperature limit performance is enhanced compared with Example 8, both reaching -30°C; and their low temperature performance before and after aging is not much different; but the peel strength before and after aging is reduced compared with that of Example 8.

[0199] Compared with Example 8, Examples 17 and 18 increase the dosage of asphalt softening oil to 7PHR and 9PHR respectively, and their extreme low temperature performance and low temperature performance before and after aging are reduced compared with the waterproofing membrane of Example 8. The peeling strength of the waterproofing membrane of Example 18 before and after aging is significantly reduced compared with the waterproofing membrane of Example 8, but the peeling strength of the waterproofing membrane of Example 17 is enhanced, indicating that the dosage of asphalt softening oil is maintained at least at 5-7PHR to improve the peeling strength performance of the waterproofing membrane.

[0200] Compared with Example 8, Examples 19 and 20 respectively reduce the amount of styrene-butadiene rubber, i.e., SBR, in Examples 19 and 20. The extreme low-temperature performance of the waterproof membranes corresponding to Examples 19 and 20 is consistent with that of Example 8, but their low-temperature performance after aging decreases; the peel strength of the waterproof membranes of Examples 19 and 20 is significantly decreased; the comparison between Examples 19 and 20 and Example 8 shows that keeping SBR within a limited range can make the waterproof have better low-temperature resistance and peel strength.

[0201] Comparing Examples 21 and 22 with Example 8, Examples 21 and 22 increase the amount of rubber powder to 40 PHR and 46 PHR, respectively. The extreme low temperature performance of the waterproof membranes corresponding to Examples 21 and 22 is consistent with the extreme low temperature performance of the waterproof membrane of Example 8, and the low temperature performance after aging for 7 days and 14 days is not much different; the peel strength of the waterproof membranes of Examples 21 and 22 is reduced, indicating that adding more rubber powder will have an adverse effect on the low temperature resistance and peel strength performance of the waterproof membrane.

[0202] Comparing Examples 23 and 24 with Example 8, Examples 23 and 24 reduce the powder to 52 PHR and 64 PHR respectively, and the extreme low temperature performance of the waterproof membranes of Examples 23 and 24 is consistent with that of Example 9, both of which are -29°C; but the low temperature performance after aging is quite different, and the peel strength of the waterproof membranes of Examples 23 and 24 before and after aging is relatively significantly lower than that of the waterproof membrane of Example 8.

[0203] The waterproofing membrane of Example 8 is compared with the waterproofing membrane of Comparative Example 6. Compared with the self-antioxidant Sa-SBS polymer (N1) in Example 8, the SBS polymer (N8) in Comparative Example 6 does not add hindered phenol, and the content of other components remains unchanged. The low-temperature performance decay of the waterproofing membrane of Comparative Example 6 before aging and after aging for 7 days is 4°C, indicating that in the process of preparing the waterproofing membrane, not adding hindered phenol has a negative impact on the waterproofing membrane to prevent low-temperature performance decay. The peel strength of the waterproofing membrane of Comparative Example 6 is significantly reduced compared with that of Example 8.

[0204] The waterproofing membrane of Example 8 was compared with the waterproofing membrane of Comparative Example 7. Compared with the self-antioxidant Sa-SBS polymer (N1) in Example 8, the SBS polymer (N9) in Comparative Example 7 did not add hindered phenols and hydrogen peroxide, and the contents of other components remained unchanged. The low-temperature performance decay of the waterproofing membrane of Comparative Example 7 before aging and after aging for 7 days was 4°C, indicating that in the process of preparing the waterproofing membrane, not adding hindered phenols and hydrogen peroxide had a negative impact on preventing the waterproofing membrane from low-temperature performance decay. The peel strength of Comparative Example 7 was also significantly reduced compared with Example 8.

[0205] The waterproofing membrane of Example 8 is compared with the waterproofing membrane of Comparative Example 8. Compared with the self-antioxidant Sa-SBS polymer (N1) in Example 8, the SBS polymer (N10) in Comparative Example 8 does not add formic acid and hindered phenol, and the content of other components remains unchanged. The low temperature performance of the waterproofing membrane of Example 8 before aging and the low temperature performance after aging for 7 days are attenuated by 2°C, and the low temperature limit of the waterproofing membrane of Comparative Example 8 before aging is 24°C, which is 5°C lower than the low temperature limit of the waterproofing membrane of Example 8 before aging of 29°C, indicating that in the process of preparing the waterproofing membrane, if formic acid and hindered phenol are not added, the hindered phenol will not modify the SBS, which will have a negative impact on the limit of the low temperature performance of the self-antioxidant Sa-SBS asphalt waterproofing membrane. The peel strength of Comparative Example 8 is also significantly reduced compared with Example 8.

[0206] The waterproofing membrane of Example 8 is compared with the waterproofing membrane of Comparative Example 9. Compared with the self-antioxidant Sa-SBS polymer (N1) in Example 8, the SBS polymer (N11) in Comparative Example 9 only adds hindered phenol, without adding formic acid and hydrogen peroxide, and the content of other components remains unchanged. The low temperature performance of the waterproofing membrane of Comparative Example 9 before aging and the low temperature performance attenuation after aging for 7 days is 6°C. The low temperature limit of the waterproofing membrane of Comparative Example 9 before aging is -24°C, which is 5°C lower than the low temperature limit of the waterproofing membrane of Example 8 before aging, which is -29°C, indicating that in the process of preparing the waterproofing membrane, SBS is dissolved in toluene, only hindered phenol is added, without adding formic acid and hydrogen peroxide, and no modification is performed, which has a negative impact on the low temperature performance limit of the waterproofing membrane and the prevention of low temperature performance attenuation. The peel strength of Comparative Example 9 shows a more obvious decrease compared with Example 8, indicating that adding hindered phenol and not adding formic acid and hydrogen peroxide cannot effectively improve the peel strength of the waterproofing membrane.

[0207] The waterproofing membrane of Example 8 is compared with the waterproofing membrane of Comparative Example 10. Compared with the self-antioxidant Sa-SBS polymer (N1) in Example 8, the SBS polymer (N12) in Comparative Example 10 does not add formic acid, hydrogen peroxide and hindered phenol, and the content of other components remains unchanged. The low temperature performance of the waterproofing membrane of Comparative Example 10 before aging and the low temperature performance after aging for 7 days are attenuated by 6°C; the low temperature limit of the waterproofing membrane of Comparative Example 10 before aging is -24°C, which is 5°C lower than the low temperature limit of the waterproofing membrane of Example 8 before aging, which is -29°C; it shows that in the process of preparing the waterproofing membrane, formic acid, hydrogen peroxide and hindered phenol are not added, and SBS is only dissolved in toluene without modification, which has a significant negative impact on the extreme low temperature performance of the waterproofing membrane and the prevention of low temperature performance attenuation. The peel strength of Comparative Example 10 shows a more obvious decrease compared with Example 8, indicating that the peel strength of the waterproofing membrane cannot be effectively improved without adding hindered phenol, formic acid and hydrogen peroxide.

[0208] The waterproof membrane of Example 8 is compared with the waterproof membrane of Comparative Example 11. The SBS in Comparative Example 11 is not chemically modified compared to the self-antioxidant Sa-SBS polymer (N1) in Example 8, and the other components remain unchanged. The low-temperature performance decay of the waterproof membrane of Example 8 before aging and after aging for 7 days is 2°C, and the low-temperature performance decay of the waterproof membrane of Comparative Example 11 before aging and after aging for 7 days is 7°C. This shows that the self-antioxidant Sa-SBS polymer modified with hindered phenol can significantly help the waterproof membrane prevent low-temperature performance decay, and can also improve the low-temperature limit. The peel strength of Comparative Example 11 also shows a relatively obvious decrease compared with Example 8, and the decrease in the peel strength of the waterproof membrane before and after aging is more obvious.

[0209] Comparing the waterproofing membranes of Example 8 and Comparative Example 12, the SBS in Comparative Example 12 is not chemically modified compared to the self-antioxidant Sa-SBS polymer (N1) in Example 8, and the amount of unmodified SBS is increased in Comparative Example 12, while the contents of other components remain unchanged. The low temperature before aging and the low temperature performance decay of the waterproofing membrane of Example 8 after aging for 7 days are 2°C. The low temperature before aging and the low temperature performance decay of the waterproofing membrane of Comparative Example 12 after aging for 7 days are 6°C. The low temperature limit before aging of the waterproofing membrane of Comparative Example 12 is -29°C, which is consistent with the low temperature limit temperature of the waterproofing membrane of Example 8 before aging, indicating that the SBS that has not been chemically modified with hindered phenol needs to increase the amount of SBS to achieve a better low temperature limit. It also shows that the SBS modified with hindered phenol is helpful for preventing the low temperature performance decay of the waterproofing membrane, and can also improve the low temperature limit. It also shows that under the requirements of the same waterproof and low temperature limit of the waterproofing membrane, the amount of the self-antioxidant Sa-SBS polymer of the embodiment of the present application is less, the cost will be relatively reduced, and the aging resistance is also better. Due to the addition of a larger amount of SBS, the peel strength of the waterproof membrane of Comparative Example 12 increased significantly compared with Example 8, and the difference in the peel performance of the waterproof membrane before and after aging decreased significantly.

[0210] Comparing the waterproofing membranes of Example 8 and Comparative Example 13, the SBS in Comparative Example 13 is not chemically modified compared to the self-antioxidant Sa-SBS polymer (N1) in Example 8, and the amount of asphalt softening oil is increased, while the contents of other components remain unchanged. The low temperature performance attenuation of the waterproofing membranes of Example 8 and Comparative Example 13 before aging and after aging for 7 days is 2°C. The low temperature limit of the waterproofing membrane of Comparative Example 13 before aging is -24°C, which is 5°C lower than the low temperature limit of -29°C before aging in Example 8, indicating that the self-antioxidant Sa-SBS polymer modified by hindered phenol is helpful in preventing low temperature performance attenuation and can also improve the low temperature limit. Although the attenuation of low temperature resistance before and after aging is less than that of Example 8, the extreme low temperature performance of the waterproofing membrane will be significantly reduced after aging for 14 days by increasing the amount of asphalt softening oil. Compared with the waterproofing membrane of Example 8, the peeling strength of the waterproofing membrane of Comparative Example 13 has decreased significantly, and the peeling strength of the waterproofing membrane before and after aging has decreased more significantly.

[0211] By comparing the above comparative examples with the embodiments, it can be seen that the self-antioxidant Sa-SBS polymer containing hindered phenol groups after chemical modification can effectively improve the extreme low temperature performance of the waterproof membrane and reduce low temperature attenuation, thereby improving the aging resistance.

[0212] The self-antioxidant Sa-SBS polymer of the present application uses hindered phenols to introduce SBS for grafting as a functional group to improve performance, so that the extreme low temperature performance of the waterproof roll can reach 32°C, and the low temperature limit after 7d aging is -29°C. The waterproof roll product shows better low temperature flexibility before aging, and after 7d of thermal oxidative aging, the limit of the low temperature flexibility of the waterproof roll can still be maintained at 27°C to -29°C. And compared with the self-antioxidant Sa-SBS polymer modified with hindered phenols in the present application, the aging and low temperature resistance of the asphalt coating obtained by the unmodified SBS is worse under the same addition amount. Therefore, the self-antioxidant Sa-SBS polymer containing hindered phenols used in the present application can achieve the effect of reducing costs on the one hand, and on the other hand, because the phenolic hydroxyl functional groups contained on the surface of the self-antioxidant Sa-SBS polymer containing hindered phenols can react with some oxygen-containing functional groups on the surface of asphalt to form a network cross-linked structure, which increases the compatibility between asphalt and each component and prevents the roll from phase separation during storage. Moreover, the presence of phenolic hydroxyl groups provides the self-antioxidant Sa-SBS polymer material with certain low-temperature and antioxidant capabilities. The benzene ring structure and long aliphatic side chains provide excellent aging resistance and good flexibility, improving the problem of a sharp decline in aging resistance.

[0213] The above is only a specific implementation method of the present application. Those skilled in the art can clearly understand that for the convenience and simplicity of description, the specific working process described above can refer to the corresponding process in the aforementioned method embodiment, and will not be repeated here. It should be understood that the protection scope of the present application is not limited to this. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application.

Claims

1. A self-antioxidant Sa-SBS polymer having the following general structural formula: (1) In formula (1), n=1~18; a+d=450~1400, b+c=1900~5700.

2. The self-antioxidant Sa-SBS polymer according to claim 1, at least one of the following is satisfied: The mass ratio of styrene chain segment to butadiene chain segment is 3-3.5:6.5-7, and the content of alkenyl functional group is ≤5%; The grafting rate of hindered phenol is 0.2% to 5.0%.

3. The method for preparing the self-antioxidant Sa-SBS polymer according to claim 1, characterized in that: include: Dispersing 20 PHR to 30 PHR of SBS with 100 PHR of a solvent capable of dissolving SBS to obtain an SBS dispersion; Adding 10 PHR to 15 PHR of formic acid and 10 PHR to 15 PHR of hydrogen peroxide to the SBS dispersion, mixing and keeping warm to obtain a reaction mixture; 1 PHR to 5 PHR of hindered phenol is added to the reaction mixture and the temperature is raised to 80° C. to 100° C. to react to obtain a self-antioxidant Sa-SBS polymer.

4. The method for preparing the self-antioxidant Sa-SBS polymer according to claim 3, characterized in that: The SBS is a polystyrene-butadiene-styrene triblock polymer, the molecular weight of the SBS is 150,000 to 450,000, and the mass content of the styrene segment in the SBS is 20% to 30%; and / or The hindered phenol is selected from the reaction product of β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionic acid and C1-C18 alkyl alcohol.

5. The method for preparing the self-antioxidant Sa-SBS polymer according to claim 3, characterized in that: The hindered phenol is selected from methyl β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, n-octadecanol β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, n-dodecyl β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate, n-octyl β-(4-hydroxyphenyl-3,5-di-tert-butyl) propionate or a combination thereof.

6. The method for preparing the self-antioxidant Sa-SBS polymer according to claim 3, characterized in that: Also includes: The prepared self-oxidation-resistant Sa-SBS polymer is added into the cooling liquid to cool the self-oxidation-resistant SBS polymer for forming: The self-oxidation-resistant Sa-SBS polymer and the cooling liquid are filtered to remove unreacted organic matter and the cooling liquid.

7. A SBS asphalt coating composition, characterized in that: include: 100 PHR asphalt, the asphalt is selected from 70# asphalt, 90# asphalt or a combination thereof; 5PHR~10PHR asphalt softening oil; 3PHR to 5PHR of the self-antioxidant Sa-SBS polymer according to claim 1 or 2, or the self-antioxidant Sa-SBS polymer prepared by the preparation method according to any one of claims 3 to 6; 2PHR~4PHR styrene butadiene rubber; 30PHR~50PHR rubber powder, the rubber powder is 60-80 mesh tire rubber powder; 50PHR-70PHR powder, wherein the powder is selected from heavy calcium powder, ore powder, concrete stone powder, talcum powder or a combination thereof.

8. The SBS asphalt coating composition according to claim 7, characterized in that: The asphalt softening oil is selected from at least one of base oil, naphthenic oil, soybean oil and aromatic oil; and / or The rubber powder has a rubber content of 30% to 50% by mass and an ash content of 10% to 30% by mass; and / or The powder is 180-200 meshes.

9. A method for preparing SBS asphalt coating material, characterized in that: The method is prepared by using the SBS asphalt coating composition as claimed in claim 7 or 8; comprising: Dispersing 100 PHR of the asphalt and 5 PHR to 10 PHR of the asphalt softening oil uniformly and heating to 130° C. to 155° C. to obtain an asphalt dispersion; Adding 3PHR to 5PHR of the self-antioxidant Sa-SBS polymer and 2PHR to 4PHR of the styrene-butadiene rubber to the asphalt dispersion and heating the mixture to 160° C. to 180° C. to obtain a blend containing the self-antioxidant Sa-SBS polymer and the styrene-butadiene rubber; To the blend containing the self-antioxidant Sa-SBS polymer and styrene-butadiene rubber, 30PHR-50PHR of the rubber powder and 50PHR-70PHR of the powder are added and the mixture is heated to 180°C-190°C and dispersed evenly to obtain SBS asphalt coating material.

10. The method for preparing the SBS asphalt coating material according to claim 9, characterized in that: The step of adding 30PHR to 50PHR of the rubber powder and 50PHR to 70PHR of the powder material to the blend containing the self-oxidative Sa-SBS polymer and styrene-butadiene rubber and heating the mixture to 180° C. to 190° C. to disperse the mixture uniformly comprises: Adding 30 PHR to 50 PHR of rubber powder to the blend containing the self-antioxidant Sa-SBS polymer and styrene-butadiene rubber and heating to 180° C. to 190° C. for dispersion to obtain a blend containing rubber powder; Add 50PHR to 70PHR of powder to the blend containing rubber powder and keep the temperature at 180℃ to 190℃ until it is evenly dispersed to obtain SBS asphalt coating material: or Adding 50 PHR to 70 PHR of powder to the blend containing the self-antioxidant Sa-SBS polymer and styrene-butadiene rubber and heating to 180° C. to 190° C. until the mixture is evenly dispersed to obtain a blend containing powder; 30PHR-50PHR of rubber powder is added to the blend containing the powder and maintained at 180°C-190°C until it is evenly dispersed to obtain SBS asphalt coating material.

11. A SBS asphalt coating material, characterized in that: Prepared according to the preparation method of claim 9 or 10.

12. A waterproof roll material, characterized in that: include: Main reinforcement substrate; An SBS asphalt coating formed from the SBS asphalt coating composition according to claim 7 or 8 or an SBS asphalt coating prepared according to the method for preparing an SBS asphalt coating according to claim 9 or 10, which is applied to at least one side of the main reinforced substrate; And an isolation protection layer covering the SBS asphalt coating material.